Considerations for oral and dental tissues in holistic care during long-haul space flights - Bakr, Mahmoud M.; Caswell, Gabrielle M.; Hussein, Habiba; Shamel, Mohamed; Al-Ankily, Mahmoud M. (Frontiers in Physiology, 2024)
The health of astronauts during and after the return from long haul space missions is paramount. There is plethora of research in the literature about the medical side of astronauts’ health, however, the dental and oral health of the space crew seem to be overlooked with limited information in the literature about the effects of the space environment and microgravity on the oral and dental tissues. In this article, we shed some light on the latest available research related to space dentistry and provide some hypotheses that could guide the directions of future research and help maintain the oral health of space crews. We also promote for the importance of regenerative medicine and dentistry as well highlight the opportunities available in the expanding field of bioprinting/biomanufacturing through utilizing the effects of microgravity on stem cells culture techniques. Finally, we provide recommendations for adopting a multidisciplinary approach for oral health care during long haul space flights.